Evaluating Offsite Technologies for Affordable Housing. (2017) - Nanyam, V.P.S. Nihar; Sawhney, Anil; Gupta, Prateek Arun
Abstract: Availability of an attribute-based evaluation and selection system for offsite technologies is crucial for the adoption of these technologies in mass housing projects. Due to this gap, adoption of offsite technologies remains low in the Indian construction industry in spite of a huge requirement of 18.78 million housing units to be built by 2022. The traditional 'sticks and bricks' approach is not likely to fulfil this demand. Adoption of offsite technologies has to be looked into as an option to deliver the extensive requirement in the area of affordable housing. Rejection of technology by evaluating the first cost alone is not the desired strategy to evaluate these offsite technologies. To evaluate and adopt these offsite technologies in affordable housing segment, a holistic selection framework encompassing a set of attributes is needed. This paper identifies a holistic selection framework with a set of offsite specific attributes alongside a set of standard attributes that are mandatory and desired for the adoption of offsite technologies in the affordable housing. Simple scoring of attributes is utilized in devising the framework. This framework is tested and validated on a case study where offsite technologies are used.